Extraction Optimization, Structural Characterization, and Anti-Hepatoma Activity of Acidic Polysaccharides From Scutellaria barbata D. Don - Su, Wenwen; Wu, Leilei; Liang, Qichao; Lin, Xiaoyue; Xu, Xiaoyi; Yu, Shikai; Lin, Yitong; Zhou, Jiadong; Fu, Yang; Gao, Xiaoyan; Zhang, Bo; Li, Li; et al. (Frontiers in Pharmacology, 2022)
The Chinese herbal medicine Scutellaria barbata D. Don has antitumor effect and is used to treatment of liver cancer in the clinically. Scutellaria barbata polysaccharide (SBP) is one of the main active components extracted from Scutellaria barbata D. Don, which plays an antitumor role. However, there is still a lack of research on the effect of Extraction optimization, structural characterization, and anti-hepatoma activity of acidic polysaccharides from Scutellaria barbata D. Don. In this study, the optimal extraction conditions of SBP were determined by response surface methodology (RSM): material-liquid ratio was 1:25, the extraction time was 2 h, and the extraction temperature was 90 °C. With these conditions, the average extraction efficiency was 3.85 ± 0.13%. Two water soluble polysaccharides were isolated from Scutellaria barbata D. Don, . namely SBP-1A and SBP-2A, which were high purity, homogeneous acidic polysaccharide components with average molecular weights of 1.15 ×105 Da and 1.4 × 105 Da, respectively. The results showed that the monosaccharide constituents of the two components were fucose, galactosamine hydrochloride, rhamnose, arabinose, glucosamine hydrochloride, galactose, glucose, xylose, and mannose, the molar ratio for SBP-1A was 0.6:0.3:0.6:30.6:3.3:38.4:16.1:8:1.4, the molar ratio for SBP-2A was 0.6:0.5:0.8:36.3:4.4:42.7:9.2:3.6:0.7. In addition, SBP-1A and SBP-2A contained uronic acid, β-glucan, the residue on the polysaccharide was mainly pyranose. The results in vitro showed that the anti-hepatoma activity of SBP-2A is better than SBP-1A and SBP. Besides, SBP-2A significantly enhanced HepG2 cells death, as cell viability was decreased, and SBP-2A induced HepG2 cell apoptosis and block the G1 phase. Further results showed that 50mg/kg SBP-2A inhibit the growth of tumor of H22 tumor-bearing mice, the average inhibition rate of that was 40.33%. This phenomenon was coupled with the up-regulated expression of P53, as well as the down-regulated expression of the cell cycle regulating gene CyclinD1 in vitro and in vivo study. Taken together, SBP-2A isolated and purified from Scutellaria barbata showed good anti-tumor activity in vivo and in vitro, SBP-2A may be a candidate drug for more evaluation in cancer prevention. This experiment provides a clue for farther studies on the molecular mechanism of its anti-hepatoma activity.